Prevalence and treatment of bovine mastitis in a dairy herd - Monteiro, Caroline Rosa; Vieira Lopes Zuchi, Tainá Luana; Pivatto, Rodrigo Antônio; Lettieri Teixeira, Mário (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The aim of this study was to conduct an epidemiological survey in cases of mastitis in a dairy herd, from January 2013 to June 2014. Mechanical milking was done twice a day. Based on animals records, 43 cases of mastitis were recorded in 2013 compared to 31 by June 2014. In 2013, 37.21% of the cases occurred in the left posterior teat (LPT), 25.58% in the right anterior teat (RAT), 20.93% in the left anterior teat (LAT) and 16.28% in the right posterior teat (RPT). In 2014, 41.94% of the cases were in the LAT, 29.03% in the RAT, 16.13% in the LPT and 12.9% in the RDT. Regarding the common used drugs, in 2013, cloxacillin (24.53% of cases), sulfadiazine+trimethoprim (SDZ + TRIM) and gentamicin (20.75% of cases) were the most used. In 2014, cloxacillin and SDZ + TRIM were used in 28.57% of the cases, and gentamicin in 22.86%. We conclude that the mastitis predisposing condition that affects the herd is the negligence of the milker cleaning and disinfecting the teats.